The influence of psychosocial work environment, personal perceived health and job crafting on nurses' well-being: a cross-sectional survey study - Xin Zhang; Chen Zhang; Jiayan Gou; Shih-Yu Lee (BMC, 2024)
Abstract Background The World Health Organization urged governments to prioritize the health and work well-being of nursing staff by promoting a positive working environment. A safe and healthy physical and psychosocial work environment is a basic human right for nurses. Job crafting is a necessary skill when facing challenging working conditions. Objectives This cross-sectional correlational research based on the Job Demands-Resources Model aimed to explore the correlation between psychosocial work environment and work well-being among nurses working in the intensive care unit (ICU) and determine whether personal perceived health could mediate the relationship and whether job crafting can moderate the mediating effect. The study hypothesized that: 1. The psychosocial work environment would impact nurses' work well-being; 2. Personal perceived health would play a role as a mediator in the relationship between psychosocial work environment and work well‐being; 3. Job crafting would moderate the relationship between personal perceived health and work well‐being. Methods A total of 655 registered nurses (RNs) from 7 ICUs in a teaching hospital in Beijing participated in this study. The RNs completed a battery questionnaire measuring their health, psychosocial work environment, well-being, and job crafting. PROCESS macros analysis was used to test mediating and moderating effects. Results Personal perceived health mediated the relationship between psychosocial work environment and work well-being (b = 0.012, 95% CI [0.008, 0.016]). The moderated mediated analysis revealed that job crafting moderated perceived health's impact on work well-being (b = -0.007, 95% CI [− 0.010, − 0.003]). Conclusion A better psychosocial work environment with well-designed work organization and job content through job crafting could positively impact nurses' health and work well-being.